2023
DOI: 10.3390/ani13050934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palm Kernel Cake Supplementation on Voluntary Feed Intake, In Situ Rumen Degradability and Performance in Buffaloes in the Eastern Amazon

Abstract: The objective was to evaluate the effects of palm kernel cake (PKC) supplementation on voluntary feed intake, in situ rumen degradability and performance in the wettest (WS—January to June) and less rainy seasons (LR—July to December) in the eastern Amazon. A total of 52 crossbred buffaloes that were neither lactating nor gestating were used, with 24 for the LR, aged 34 ± 04 months and an initial average weight of 503 ± 48 kg, and 24 for the WS aged 40 ± 04 months with an average weight of 605 ± 56 kg. The fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Animals supplemented with palm oil maintained consumption levels from the third cycle, while in the second and fourth cycles, they were similar to the control treatment group. Ferreira et al [ 57 ] and de Melo Lisboa et al [ 46 ] observed a reduction; Rodrigues et al [ 5 ] and Amaral-Júnior et al [ 10 ] observed an increase in consumption; and Galvão et al [ 58 ] and Salt et al [ 59 ] found no difference. These variations in consumption may be related to the level of inclusion of fat and fiber content in the material used; as they are co-products, there is no homogeneity in the composition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Animals supplemented with palm oil maintained consumption levels from the third cycle, while in the second and fourth cycles, they were similar to the control treatment group. Ferreira et al [ 57 ] and de Melo Lisboa et al [ 46 ] observed a reduction; Rodrigues et al [ 5 ] and Amaral-Júnior et al [ 10 ] observed an increase in consumption; and Galvão et al [ 58 ] and Salt et al [ 59 ] found no difference. These variations in consumption may be related to the level of inclusion of fat and fiber content in the material used; as they are co-products, there is no homogeneity in the composition.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the energy density of supplements containing co-products was higher due to the increase in fat. The ether extract in palm kernel cake ranges from 5.7 to 13.55% and in coconut cake between 17.08 and 26.43 [ 5 , 10 , 57 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations